Tintigny meteorite: the first Belgian achondrite. (December 2021) - Pourkhorsandi, Hamed; Debaille, Vinciane; Gattacceca, Jérôme; Greenwood, Richard; Leduc, Thierry; De Ceukelaire, Marleen; Decrée, Sophie; Goderis, Steven
Abstract: A late afternoon in February 1971, a meteorite impacted the rooftop of a house in Tintigny village in southern Belgium. Confirmed as a possible meteorite by the schoolteacher, the meteorite and its fall story did not leave the village. Finally, 46 years after the fall event, we got the opportunity to study and characterize this meteorite. In this work, we give a detailed report on its textural, mineralogical, whole-rock elemental and oxygen isotopic composition. Officially named as Tintigny, we classified it as an achondrite from howardite-eucrite-diogenite (HED) clan and more precisely a polymict eucrite. A brecciated basaltic rock believed to be originated from the surface of V-type asteroids namely the asteroid 4 Vesta. Tintigny has recorded the evidence of the impact metamorphism and metasomatism processes active on its parent body. Tintigny is one of the 39 eucrite falls known to date, and one of the 11 eucrites occurred in Europe. It is the fifth officially recognized meteorite and the first achondrite from Belgium. This report shows the importance of studying and accessing such a meteorite for further cosmochemical and planetary investigations and enriching our knowledge on the formation of HED meteorites and their parent bodi(es). In addition, it brings the attention to its importance as a scientific heritage that has to be properly understood and safeguarded for the generations of scientists, scholar, and amateurs to come. Highlights: Tintigny meteorite fell in February 1971 in a village in southern Belgium. Based on our multimethod study, we classified it as a polymict eucrite. This type of meteorites are achondrites from howardite-eucrite-diogenite (HED) clan. HED meteorites are believed to originate from the surface of the asteroid 4 Vesta. Tintigny is one of the 39 eucrite falls known to date.